The effect of deficit irrigation on the grain yield of dry bean (Phaseolus vulgaris L.) in semiarid regions - Ucar, Y.; Kadayifci, A.; Yilmaz, H. İ.; Tuylu, G. İ.; Yardimci, N. (Spanish Journal of Agricultural Research, 2009)
The aim of this study was to determine the optimum water use of the dry bean (Phaseolus vulgaris L.). Such information is needed by planners and producers for the design of irrigation schemes to minimise yield reductions under water deficit conditions. Under the present experimental conditions, high grain yields were obtained by meeting the full water needs of the crop (1.94-2.43 Mg ha-1), by meeting 75% of their needs (1.92-2.40 Mg ha-1), or by irrigation throughout the growing season except during ripening (1.93-2.23 Mg ha-1). Grain yields were reduced when irrigation water was not provided during the flowering and yield formation periods, and did not increase significantly in such cases even if water had been supplied during the establishment, vegetative, and ripening periods. The yield response factors for the entire growing season, and for the vegetative, flowering, yield formation and ripening periods, were 1.28, 0.36, 0.84, 0.80, and 0.08 respectively. Thus, to achieve effective vegetative production in semiarid regions such as Isparta, irrigation is absolutely necessary. Under limited water conditions, a water deficit of 25-50% is tolerable throughout the growing season, or during the vegetative and ripening periods.